2022
DOI: 10.1111/ced.15384
|View full text |Cite
|
Sign up to set email alerts
|

Comorbidities in Chilean patients with psoriasis: a Global Healthcare Study on Psoriasis

Abstract: Background Psoriasis is a chronic inflammatory skin disease associated with several important medical comorbidities. There are scant data available on the comorbidities of patients with psoriasis in South America. Aim To examine the comorbidity profile of adult patients with psoriasis in Chile and its association with severity of psoriasis. Methods This was a multicentre, cross‐sectional study involving 16 hospitals and clinics in Chile, which used a 48‐item questionnaire to study clinician‐ and patient‐report… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…Forty-one studies [12–14,18,33–69] were included in the meta-analysis that 19 studies were case–control studies and 22 studies had no control groups (Table 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Forty-one studies [12–14,18,33–69] were included in the meta-analysis that 19 studies were case–control studies and 22 studies had no control groups (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…TSA showed that the analysis of OR included sufficient cases and there was a publication bias across the studies for the calculation of pooled ER and OR. [34] Turkey Caucasian 20/250 -44 MSP US, liver test, exclusion of other liver diseases Fahim, 2023 [35] Pakistan Asian 30/80 16/80 38 CPP US, liver test, exclusion of other liver diseases Ruan, 2022 [39] China Asian 96/148 4018/5524 38.8 NR US, liver test, exclusion of other liver diseases Ghafoor, 2021 [12] Pakistan Asian 53/101 29/101 46.4 NR US, liver test, exclusion of other liver diseases Gau, 2022 [36] China Asian 1191/5591 295,749/1,479,360 50.4 NR US, liver test, exclusion of other liver diseases Inci, 2016 [37] Turkey Caucasian 32/60 21/60 44.5 CPP US, liver test, exclusion of other liver diseases Lee, 2019 [38] China Asian 34/307 ->18 NR Not described Valenzuela, 2022 [40] Chile Mixed 28/598 -49.2 Mixed Not described Gandha, 2020 [41] Indonesia Asian 28/36 -40.1 Vulgaris US, liver test, exclusion of other liver diseases Shibata, 2022 [46] Japan Asian 13/46 14/138 50.6 Mixed US, liver test, exclusion of other liver diseases Li, 2022 [44] China Asian 46/127 -46.5 PsA US, liver test, exclusion of other liver diseases Yadav, 2023 [47] India Asian 17/50 2/50 38.9 CPP US, liver test, exclusion of other liver diseases Ho, 2019 [43] China Asian 58/223 -58 PsA US, liver test, exclusion of other liver diseases Ortolan, 2019 [45] Italy Caucasian 40/76 -57.7 PsA US, liver test, exclusion of other liver diseases Gisondi, 2016 [42] Italy Caucasian 55/124 21/79 55 CPP US, liver test, exclusion of other liver diseases Gisondi, 2009 [13] Italy [51] China Asian 34/307 ->18 NR Not described Magdaleno-Tapial, 2020 [52] Spain [58] India Asian 17/61 5/24 46 CPP US, liver test, exclus8ion of other liver diseases…”
Section: Discussionmentioning
confidence: 99%
“…The Global Healthcare Study on Psoriasis (GHSP) is a multi-country, multi-centre, longitudinal observational study that collects cross-sectional data. This research project is an ongoing international, global survey performed since January 2020 in multiple countries across several continents ( 15 , 21 ). Socio-demographic and psoriasis-related disease and treatment data were obtained from 2 specialized dermatology centres in Europe (Switzerland), 31 in Latin America (Brazil and Chile), 4 in Asia (China and Singapore), and 1 in North America (USA).…”
Section: Methodsmentioning
confidence: 99%
“…Many patients achieve full or almost full skin clearance when treated with biologics, which often leads to considerable improvement in their quality of life ( 14 ). However, access to modern treatment, and impairment due to comorbidities, vary enormously worldwide ( 15 ). The availability of treatment resources is especially limited in low-income countries and for people with low socio-economic status.…”
mentioning
confidence: 99%
“…On the other hand, NAFLD is more common in patients with moderate to severe psoriasis and its course is then more severe [151][152][153]. Several studies revealed that psoriasis is an independent risk factor for liver diseases [154][155][156][157][158][159][160][161][162][163][164][165][166][167][168][169]. All patients with psoriasis, including children and adolescents, should have NAFLD screening and be appropriately consulted by a hepatologist to detect the first symptoms early and prevent further liver damage.…”
Section: Non-alcoholic Fatty Liver Diseasementioning
confidence: 99%